Summation of Large Numerousness by Newborn Chicks - Rugani, Rosa; Regolin, Lucia; Vallortigara, Giorgio (Frontiers in Psychology, 2011)
Newly-hatched domestic chicks, reared with identical objects, when presented with sets of 3 vs. 2 objects disappearing one-by-one behind separate screens, spontaneously inspected the screen occluding the larger set; even when the continuous variables (area or perimeter) were controlled for (Rugani et al., 2009). Here, using a similar paradigm, we investigated the ability of chicks to perform addition on larger sets of objects. Chicks imprinted on 5 identical objects, were presented at test with 6 vs. 9 objects which disappeared one-by-one (Exp.1). In Exp. 2, the same overall number of objects (15) was used, but employing an increased ratio, i.e. 5 vs. 10. In both experiments, when continuous variables were not made equal, chicks spontaneously inspected the screen occluding the larger set. However, when the size of the objects was adjusted so as to make the total surface area or perimeter equal for the two sets, chicks did not exhibit any preference. Lack of choice in the control conditions could be due to a combination of prefences; to rejoin the larger numerousness as well as the bigger objects (Rugani et al., 2010). In Exp. 3, chicks were familiarized, during imprinting, with objects of various dimensions, in an attempt to reduce or suppress their tendency to approach objects larger than the familiar ones. Again chicks failed to choose at test between 5vs.10 objects when continuous variables were made equal. Results showed that chicks, after a one by one presentation of a large number of objects, rejoined the larger set. In order to choose the larger set, chicks estimated the objects in the two sets and then compared the outcomes. However, differently to what has been described for small numerousness, chicks succeeded only if non-numerical cues as well as numerical cues were available. This study suggests that continuous variables are computed by chicks for sets of objects that are not present at the same time and that are no longer visible at the time of choice.